The effects of warm-up and pre-cooling on endurance performance in high ambient temperatures - Ückert, S.; Joch, W. (New Studies in Athletics, 2007)
It is well established that warm conditions have a detrimental effect on endurance performance. If skin temperature is exceeded by the ambient temperature, heat dissipation is impaired and heat storage is likely to occur. A warm-up, which by definition entails increasing body temperature, is generally considered a vital part of the preparation for competition - including endurance performances in hot weather. On this understanding, the question arises if cooling prior to competition (pre-cooling) might be a better alternative. Twenty subjects performed two laboratory endurance tests in conditions of high ambient temperature and relative humidity. One test followed a 20-minute warm-up and the other a 20-minute pre-cooling procedure. The comparison of results shows that pre-cooling significantly extends the time to exhaustion and slows the increase in both body core temperature and heart rate. The authors conclude that pre-cooling, as opposed to a warm-up, optimises thermoregulatory processes before physical effort in warm conditions.